Universal Design for Learning pada Praktik Pendidikan Inklusif: Analisis Sistematis terhadap Model, Strategi, dan Dampaknya di Sekolah - Azizah, Aulia; Wulandari, Rani; Putra, Andi Dewangga Permana (Jurnal Ilmiah Wahana Pendidikan, 2025)
Universal Design for Learning (UDL) is a curriculum design framework that aims to accommodate learner diversity through flexibility in material representation, ways of acting and expressing competencies, and learning engagement. This study conducted a Systematic Literature Review (SLR) of 15 international scientific articles discussing the implementation of UDL at various levels of education. This study analyzed the conceptual model of UDL, implementation strategies, and its impact in the context of inclusive education in schools. The study results indicate that the UDL model consistently refers to three main principles: representation, action and expression, and engagement, which have been proven to improve learning accessibility, instructional differentiation, and the quality of learning interactions. The most common implementation strategies include the provision of multimodal materials, alternative assessment options, student interest-based adaptations, and the integration of assistive technology. The positive impact of UDL is seen in increased student engagement, learning effectiveness for students with special needs, and teacher competency in designing inclusive learning, although long-term quantitative evidence is still limited. This study confirms that UDL has significant potential to support inclusive education practices. However, optimal implementation requires teacher training, institutional support, and ongoing evaluation.